Analisis Pelaksanaan Prosedur Penahanan Terhadap Penyalahgunaan Zat Adiktif Dan Psikotropika Di Direktorat Narkoba Kepolisian Daerah Sumatera Selatan - Simanjuntak, Doli Agum; Idi, Abdullah; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2021)
Drug crime investigation is a series of investigators' actions in terms of and according to the method regulated by law to seek and collect evidence which with that evidence makes clear about the criminal act that occurred and in order to find the suspect. The problems that have been identified include: 1) There is still a lack of investigators for drug crimes when compared to the number of drug crimes cases which are increasing every year; 2) The minimum budget provided for the operational costs of investigating drug crimes so that it can hinder the investigation of drug crimes; 3) Inadequate facilities and infrastructure so that it interferes and hinders investigators in uncovering drug crime cases. The purpose of this study was to analyze the Implementation of Detention Procedures Against the Abuse of Addictive and Psychotropic Substances at the Drug Directorate of the South Sumatra Police. This study uses a qualitative approach where the results can be seen that the Planning (Planning) planning process is very good, it can be seen from the objectives, human resources along with the facilities and infrastructure that have been available, all have been aligned with the work program and vision and mission to be achieved, especially in the implementation of detention procedures against suspected of abuse of addictive substances and psychotropic substances, Organization (Organization) with indicators of organizational structure and division of tasks is very good that in each unit division and members have very clear knowledge of the main tasks and functions that they will do so that the process in compiling performance programs for all can be measured and run thoroughly in the implementation of the containment procedure for the abuse of addictive and psychotropic substances. Movement (Actuating) looks good using standard operating procedure indicators and delegation of authority where coordination when carrying out tasks continues by prioritizing existing SOPs, as well as coordination in assigning tasks to members based on a track record of tasks that can be completed to get the authority to carry out tasks. Monitoring (Controlling) has indicators of responsibility and reporting has been fully successfully carried out by members and officers both on work responsibilities and reporting of completeness of performance in implementing procedures for detention of addictive and psychotropic substance abuse.